Aplikasi Diferensial dalam Menghitung Analisis Keuntungan Maksimal pada UMKM - Puspaningrum, Cici (Digital Business Progress, 2024)
Business is an economic activity in which goods and services are produced, bought or sold  for  maximum  profit.  The  profit  of  a  business  is  influenced  by  many  factors,  namely, operational costs, production costs, product selling prices, sales volume, demand and others. The purpose of this study is how to analyze the application of the derivative concept based on the maximum profit that can be obtained by UMKM Keripik Dewi. as for calculating the maximum profit, several steps are taken, namely: (1) The steps for applying the derivatives, and in this step are divided into (a) the formulation of several necessary variables, (b) carrying out the preparation of mathematical models, (c) completing the calculation of mathematical models, (2) the company getting the profit on only three products. Made, so that this company has not fully obtained the maximum profit that has the potential to be achieved.